Knowledge and practices of menstrual hygiene among nursing students in IIUM Kuantan - Zamri, Nordiana Binti Zamri; Zaw, Cho Cho (SAS Publishers (An International Publisher for Academic and Scientific Journals), 2021)
Introduction: Menstrual hygiene management include the use and proper disposal of clean menstrual management materials during menstruation while dysmenorrhea is discomfort, pain, and cramps at the uterine origin during menstruation. Objective: The objective of this study is to identify the knowledge and practices of menstruation and menstrual hygiene, screening of dysmenorrhea among nursing students in IIUM Kuantan and the relationship between the selected socio- demographic with level of knowledge and practices of menstruation and menstrual hygiene. Methodology: A cross-sectional study was conducted among 180 undergraduate nursing students in IIUM Kuantan. The questionnaires distributed consisted mainly four parts which is socio- demographic data, the level of knowledge, practices of menstruation and menstrual hygiene and screening dysmenorrhea among the respondents. Results: The result highlighted that majority of nursing students (90.6%) have good knowledge, while (74.6%) students have good practices of menstrual hygiene. High percentage of dysmenorrhea was reported among the students (89.2%). There was a significant difference between year of study and practices of menstrual hygiene (p=0.033). Conclusion: The knowledge and practices of menstruation was good among nursing students in IIUM Kuantan. However, they need to improve in certain areas regarding knowledge and practices of menstrual hygiene.